A COMPUTATIONAL APPROACH ON UNDERSTANDING STRUCTURAL INTERACTIONS OF ENVELOPE PROTEIN OF DENGUE VIRUS BOUND WITH SQUALENE, A PROTOTYPE ANTI-VIRAL COMPOUND - Chandrasekaran, Rajkuberan; Sivaraman, Thirunavukkarasu; Sivaramakrishnan, Sivaperumal; Kumar, Jayasree J. S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: The objective of the work was to validate the structural binding affinity of Squalene with the envelope protein of Dengue virus by means of molecular simulations. Methods: Three-dimensional (3D) structure of dengue 2 virus envelope protein was retrieved from Protein Data Bank PDB and Squalene compound from the ZINC database. Molecular docking between the E protein and Squalene were carried out by means of Auto Dock 4.2. Results: Based on the study, it was observed that the binding/docking energy for the complex structure was calculated to be-5.55 kcal/mol. Critical residues to interact with E protein were scrutinized by analyzing the interface of the complex within 4 Å proximity. Residues such as Thr 48, Glu49, Ala 50, Val 130, Leu 135, Ser 186, Pro 187, Thr 189, Gly 190, Leu 191, Phe 193, Leu 198, Leu 207, Thr 268, Phe 279, Thr 280, Gly 281, His 282 and Leu 283 were found to be non-covalently located around the squalene. Conclusion: Scopes to design de novo anti-viral compounds to the dengue viruses by using squalene as a new class of template structure have also been concisely brought into fore.